"Let's Talk About: Sex": development, pilot and evaluation of a positive sexual-health education group for individuals within secure ID settings. Issue 1 (29th October 2021) - Ashworth, Sarah; Carton, Hannah
Abstract : Purpose: There is a dearth of positive, proactive, sexual-health education programmes available for individuals with intellectual disabilities (IDs). This paper aims to provide an overview of the development, pilot and evaluation of a programme aimed at increasing awareness of the intricacies and risks of sexual health, intercourse and relationships. This programme covers relevant topics in a non-judgemental, informative and supportive approach. Design/methodology/approach: A pre-post comparison within-group design was used (N = 14). The programme was run separately across three in-patient ID secure services within the UK and lasted for 16 weeks. The measure used to explore change was the sexual attitudes and knowledge questionnaire (SAK; Heighway and Webster, 2007). Findings: Scores indicated improvement across all sub-factors as measured by the SAK, although no results reached statistical significance using Wilcoxon signed rank tests. Qualitative feedback indicated the benefits of this programme in relation to participants' increased knowledge and confidence. Results have been discussed in terms of both the statistical analysis and clinical implication. Originality/value: Results have been discussed in terms of statistical analysis and clinical implications with the aim of clinicians considering the programme's application and utility within various clinical contexts. Additionally, gaining insight into the process of programme development and refinement, including future directions.